Serum Neurofilament Light Levels in Patients with Cerebrotendinous Xanthomatosis: a Pilot Study - Antonio Edvan Camelo-Filho; Pedro Lucas Grangeiro Sá Barreto Lima; Rodrigo Fagundes da Rosa; Oliver R Miyajima; Matheus Henrique Brustolim Marcucci; Stephanie Suzanne de Oliveira Scott; Luis Edmundo Teixeira de Arruda Furtado; Annyta F Frota; Michelle V R Soares; Danielle S Macedo; André Pessoa; Paulo R Nóbrega; et al. (The Cerebellum, 2026)
Introduction: Cerebrotendinous xanthomatosis (CTX) is a rare autosomal recessive disorder caused by pathogenic variants in CYP27A1 , leading to cholestanol accumulation and progressive neurological dysfunction. Neurofilament light chain (NfL) is a biomarker of neuroaxonal injury in several hereditary ataxias, but its role in CTX has not been investigated. We aimed to determine whether serum NfL is elevated in CTX and whether it correlates with clinical severity. Methods: Five genetically confirmed CTX patients and five age-, sex-, and body mass index–matched healthy controls were evaluated. Clinical severity was assessed using the Scale for the Assessment and Rating of Ataxia (SARA). Serum NfL concentrations were measured using single-molecule array technology. Group comparisons were performed using the Mann–Whitney U test, and associations were assessed using Spearman’s correlation coefficient. Results: Serum NfL levels were significantly higher in CTX patients than in controls (median 14.63 pg/mL [interquartile range 5.10–18.17] vs. 2.90 pg/mL [2.52–3.56]; p = 0.008). Within the CTX group, NfL levels showed a strong positive correlation with SARA scores (Spearman's ρ = 0.90, p = 0.037), indicating higher NfL levels in patients with greater neurological impairment. Conclusion: Serum NfL is elevated in CTX and correlates with ataxia severity, supporting its potential relevance as a marker of neuroaxonal injury in this disorder. Larger longitudinal studies are needed to confirm these preliminary findings and clarify the role of NfL in disease monitoring.

Evaluation of an intra-articular carboxymethylcellulose crosslinked hydrogel in horses with osteoarthritis - R. Rinnovati; A. Spadari; A. Malpighi; F. Meistro; M.V. Ralletti; E. Marcucci; M.A. Tarasconi; R. Lo Chiatto; S. Della Tommasa (Journal of Equine Veterinary Science, 2025)

Decrease from main root canal and intratubular Fusobacterium nucleatum and its endotoxin after ultrasonic activation of conventional and alternative irrigation solutions - Mirela Cesar Barros; Victor Feliz Pedrinha; Felipe Eduardo Oliveira; Maria Cristina Marcucci; Brenda Paula F. A. Gomes; Luciane Dias de Oliveira; Flaviana Bombarda de Andrade (Biofouling, 2024)

Characterisation and transferability of transcriptomic microsatellite markers for Nothofagus species - V. El Mujtar; M. López; S. Amalfi; F. Pomponio; S. Marcucci Poltri; S. Torales (New Zealand Journal of Botany, 2017)
Discriminant molecular markers are required for research on population genetics, as well as evolutionary studies involving identification of hybrids and parental species, or detection of the genome regions under selection. We provide a set of 27 transcriptomic microsatellite markers (SSRs) for South American Nothofagus species, derived from 73 Nothofagus alpina ( = N. nervosa) annotated unigenes. Rates of cross‐amplification ranged from 22% to 37%. Genetic characterisation of 22 transcriptomic SSRs for N. alpina and N. obliqua reveals low genetic variability, due to the general occurrence of one major allele at each locus, and high specificity, with few alleles shared between species (14%). At inter‐species level 95% of loci were discriminant, with a total G''st over loci of 0.9, indicating that alleles were mostly fixed for all loci in both species. At intra‐species level the number of markers with significant differentiation was 2.5 times higher for N. obliqua than for N. alpina populations. Moreover, transcriptomic SSRs showed higher performance compared with published anonymous microsatellites isolated from genome sequences without annotation. This set of transcriptomic microsatellites will be useful to the scientific community working on conservation and evolutionary aspects of Nothofagus species.

Distribution map of Ambrosia artemisiifolia L. (Asteraceae) in Italy - R. Gentili; F. Gilardelli; E. Bona; F. Prosser; A. Selvaggi; A. Alessandrini; F. Martini; P. L. Nimis; T. Wilhalm; M. Adorni; N. M. G. Ardenghi; E. Barni; et al. (Plant Biosystems, 2017)

Seroepidemiology of HEV and HAV in two populations with different socio-economic levels and hygienic/sanitary conditions - M. Zuin; C. Caserta; L. Romanò; A. Mele; A. Zanetti; R. Cannatelli; A. Giorgini; C. Tagliacarne; A. Amante; F. Marcucci; P. M. Battezzati (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

How well do integrated assessment models represent non-CO2 radiative forcing? - Mathijs J. H. M. Harmsen; Detlef P van Vuuren; Maarten van den Berg; Andries F Hof; Chris Hope; Volker Krey; Jean-Francois Lamarque; Adriana Marcucci; Drew T Shindell; Michiel Schaeffer (Climatic Change, 2015)

Inappropriate prescription of allopurinol and febuxostat and risk of adverse events in the elderly: results from the REPOSI registry - L. Pasina; A. L. Brucato; C. D. Djade; P. Di Corato; S. Ghidoni; M. Tettamanti; C. Franchi; F. Salerno; S. Corrao; A. Marengoni; M. Marcucci; P. M. Mannucci; et al. (European Journal of Clinical Pharmacology, 2014)

The contribution of seismic data in microzonation studies for downtown L’Aquila - G. Milana; R. M. Azzara; E. Bertrand; P. Bordoni; F. Cara; R. Cogliano; G. Cultrera; G. Di Giulio; A.M. Duval; A. Fodarella; S. Marcucci; S. Pucillo; et al. (Bulletin of Earthquake Engineering, 2011)

World distribution of the T833C/844INS68 CBS in cis double mutation: a reliable anthropological marker - G. Pepe; O. Camacho Vanegas; O. Rickards; B. Giusti; P. Comeglio; T. Brunelli; R. Marcucci; D. Prisco; G. F. Gensini; R. Abbate (Human Genetics, 1999)